2012
DOI: 10.1021/jp208436j
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Origin of Piezo- and Pyroelectric Properties in Collagen Investigated by Molecular Dynamics Simulations

Abstract: Molecular dynamics simulations were used to study the effect of mechanical and thermal stimuli on the electrostatic properties of collagen model helices. Our model sequences were based on glycine proline and hydroxyproline amino acids. We find that longitudinal mechanical strain induces significant variation of the polarization of the collagen fibril. Such a phenomenon is determined by reorientation of the backbone polar groups, which are free to respond to the mechanical solicitation. This non-negligible effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 38 publications
0
32
0
Order By: Relevance
“…The intensity of the polarization in the longitudinal direction changes due to the winding/unwinding motion of the structure when the physical force of compression/tension is applied, which is a piezoelectric effect. [129] In 2016, Zhu et al reported the piezoelectric effect on the "supertwisted" collagen structure using atomistic simulation of supertwisted collagen, and verified the piezoelectric mechanism. [130] The result shows that collagen represents unidirectional polarization along the longitudinal axis of collagen fibril, and the magnitude of polarization is varied when mechanical stress is applied on the collagen due to the reorientation and magnitude change of the permanent dipoles.…”
Section: Piezoelectricity Of Proteinsmentioning
confidence: 99%
See 4 more Smart Citations
“…The intensity of the polarization in the longitudinal direction changes due to the winding/unwinding motion of the structure when the physical force of compression/tension is applied, which is a piezoelectric effect. [129] In 2016, Zhu et al reported the piezoelectric effect on the "supertwisted" collagen structure using atomistic simulation of supertwisted collagen, and verified the piezoelectric mechanism. [130] The result shows that collagen represents unidirectional polarization along the longitudinal axis of collagen fibril, and the magnitude of polarization is varied when mechanical stress is applied on the collagen due to the reorientation and magnitude change of the permanent dipoles.…”
Section: Piezoelectricity Of Proteinsmentioning
confidence: 99%
“…Each polypeptide chain possesses a characteristic major tripeptide repeat (GPX) sequence with glycine (G), proline (P), and several different amino acids (X) ( Figure a) 120–125. It was found that the piezoelectricity of collagen is due to this particular helical structure 13,126–129. The static polarization in the longitudinal direction of collagen is due to helically aligned peptide bonding and the hydroxyl group present at the side chain of hydroxyprolines.…”
Section: Piezoelectricity Of Proteinsmentioning
confidence: 99%
See 3 more Smart Citations